2022
DOI: 10.1186/s12880-022-00810-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of extramural venous invasion in rectal cancer by dynamic contrast-enhanced and diffusion weighted MRI: a preliminary study

Abstract: Background To explore the value of the quantitative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and diffusion-weighted imaging (DWI) parameters in assessing preoperative extramural venous invasion (EMVI) in rectal cancer. Methods Eighty-two rectal adenocarcinoma patients who had underwent MRI preoperatively were enrolled in this study. The differences in quantitative DCE-MRI and DWI parameters including Krans, Kep and ADC values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Chen et al discovered that the mrEMVI-positive group had significantly higher V e than the mrEMVI-negative group, but K trans showed no significant difference [ 24 ]. Wei et al demonstrated that K trans was the independent predictor of EMVI in rectal cancer [ 35 ]. However, the mean value of K ep did not show a significant difference between the EMVI-positive and EMVI-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al discovered that the mrEMVI-positive group had significantly higher V e than the mrEMVI-negative group, but K trans showed no significant difference [ 24 ]. Wei et al demonstrated that K trans was the independent predictor of EMVI in rectal cancer [ 35 ]. However, the mean value of K ep did not show a significant difference between the EMVI-positive and EMVI-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…DWI, which reflects tumor cell density and necrosis, is the only noninvasive method for detecting water molecule diffusion in living tissues, while the ADC value is a quantitative indicator of DWI [ 37 ]. Many studies have indicated that the ADC value is useful for predicting rectal cancer prognosis [ 37 , 38 ]. A study by our team [ 1 ] analyzed the correlation between T staging and ADC in 77 patients with rectal cancer, which revealed that Ki-67 expression in rectal cancer is negatively correlated with ADC.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it should be noted that the temporal resolution is estimated to be within the range of 5 to 18 seconds per phase. Subsequently, the acquisition process necessitates breath holds, which could potentially pose difficulties for certain patients and constrain the dynamic imaging’s spatial and temporal resolution and volumetric coverage ( 41 - 45 ). This study utilized GRASP radial acquisition, which improved spatial and temporal resolutions over TWIST.…”
Section: Discussionmentioning
confidence: 99%